Accumulation of plasmacytoid dendritic cell is associated with a treatment response to DNA-damaging treatment and favorable prognosis in lung adenocarcinoma - Cha, Yoon Jin; Kim, Eun Young; Choi, Yong Jun; Kim, Chi Young; Park, Min Kyung; Chang, Yoon Soo (Frontiers in Immunology, 2023)
Introduction: Favorable responses to the treatment including immune checkpoint inhibitors (ICIs) have been consistently reported in lung cancer with smoking history. As the tumor microenvironment (TME) may be involved in the treatment response to ICIs, we aimed to investigate the TME of lung cancer with different smoking status. Methods: Lung adenocarcinoma (LUAD) tissue (Tu) and adjacent normal-appearing lung tissue (NL) from current and never smokers were investigated by single-cell RNA sequencing and immunofluorescence and immunohistochemical staining. The clinical implications of identified biomarkers were validated using open-source datasets. Results: The lungs of smokers had an increased proportion of innate immune cells in NL tissues, whereas Tu tissues had a lower proportion of these cells than those of non-smokers. Monocyte-derived macrophages (mono-Mc), CD163-LGMN macrophages, monocyte-derived dendritic cells (DCs), and plasmacytoid DCs (pDCs) were significantly enriched in smokers’ Tu. Among these clusters, pDCs, specifically enriched in the Tu of smokers. The expression of representative pDC markers, leukocyte immunoglobulin-like receptor A4 (LILRA4) and Toll-like receptor 9 (TLR9), was increased in the stromal cells of LUAD in patients with a smoking history. In an animal model of lung cancer, ionizing radiation induced robust TLR9 expressing immune cells in peritumoral area. Survival analysis using a TCGA-LUAD dataset indicated that patients overexpressing pDC markers exhibited superior clinical outcomes to age-, sex-, and smoking-matched control groups. Top 25% patients with high TLR9 expression exhibited significantly higher tumor mutational burden than that of low TLR9 expression group (bottom 25% patients) (5.81 mutations/Mb vs 4.36 mutations/Mb; P = 0.0059, Welch’s two-sample t-test). Conclusions: There is an increased pDC in the TME of smokers' lung cancer, and the response of pDC to DNA damaging treatment would lead a conducive environment to ICIs containing regimens. These findings suggest that R&D that induces an increase in the activated pDC population is continuously required to enhance therapeutic effectiveness of ICIs-containing therapies in lung cancer.